Reajuste de precios en contratos de obra pública pactados en moneda extranjera frente al régimen de bandas cambiarias - López Jiménez, Enrique (2017)
The exchange rate works as a price readjustment mechanism in civil works contracts. But, the Central Bank of Costa Rica modified the system to fix the exchange rate. The exchange rate of the colon to the dollar does not produce necessarily a progressive rise of the dollar. Thus, the traditional mechanism for price readjustment does not always ensure an economic balance in civil works contracts.